Clinical characteristics of patients hospitalized for COVID-19 vaccinated with at least two doses in a tertiary care hospital in Turkey - Ayşin Kılınç Toker; Ayşe Turunç-Özdemir; Recep Civan-Yüksel; Esma Eryilmaz-Eren; İbrahim Toker; İlhami Çelik (Microbes, Infection and Chemotherapy, 2022)
Background. We aimed to examine the characteristics of Turkish patients hospitalized with COVID-19 despite being fully vaccinated. Method. A retrospective, single-center study was conducted in fully vaccinated patients with inactivated whole virion (CoronaVac) and/or BNT162b2 mRNA (Pfizer-BioNTech) vaccines and admitted to the hospital. We evaluated the hospitalized patients regarding the intensive care unit admission and death. A multivariate binary logistic regression analysis was used to determine the factors for mortality. Results. We conducted the study with 541 patients. The mean age was 70.2, and 52.1% of the patients were women. 73.6% of the patients were 65 years or older. The most common comorbidities were hypertension, diabetes mellitus, and COPD. The rate of the alpha variant was 54.3%, and the delta variant was 29.4%. The mortality rate was 45.8%, and the ICU admission rate was 55.3%. The delta (B.1.617.2) variant had higher ICU admission and mortality rate. Patients vaccinated with two-dose Sinovac-CoronaVac had a higher mortality rate. There was no difference between the time between the last vaccination dose to hospitalization, ICU admission, and mortality. LOS in the hospital was longer in ICU and mortality patients. In multivariate binary logistic analysis; age (odds ratio (OR), 1.06; 95% confidence intervals (95% CI) 1.04-1.08- year increase), male gender (OR, 1.57; 95% CI, 1.04-2.38), presence of comorbid diseases (OR, 4; 95% CI, 2-8) and delta variant (OR, 7.3; 95% CI, 4.4- 12.2) and vaccination with CoronaVac plus BioNTech (OR, 0.21; 95% CI, 0.07-0.62) were associated with death. Conclusion. Our results suggest administering a third and fourth dose of mRNA vaccine to subjects vaccinated primarily with two doses of CoronaVac.